Protective Role of Paederia foetida L. Against Hepatic Inflammatory Response in a Mice Model of Escherichia coli-Induced Sepsis - Savitri, Lisa; Freitas, Maria Do Carmo Da Costa; Prasetyawan, Fendy; Saristiana, Yuneka; Mebung, Konradus Klala; Amanda, Cornelia (Biology, Medicine, & Natural Product Chemistry, 2025)
Sepsis is a severe medical condition characterized by a systemic immune response to infection, often leading to multi-organ failure and death if not treated effectively. This study aimed to investigate the antiseptic properties of Paederia foetida leaf extract in male mice induced with sepsis using Escherichia coli. A total of 24 mice were divided into six groups: a normal group (no treatment), a negative control group (distilled water), a positive control group (ciprofloxacin), and three treatment groups receiving P. foetida leaf extract at doses of 100, 300, and 500 mg/kg BW. After 15 days of oral administration, liver tissue samples were analyzed for IL-6 expression, a pro-inflammatory cytokine associated with sepsis. The results revealed a significant reduction in IL-6 expression in the treatment groups, particularly at the 500 mg/kg BW dose. This dose showed the most effective anti-inflammatory response, with IL-6 expression levels comparable to those of the positive control group treated with ciprofloxacin. However, the 100 mg/kg BW dose demonstrated minimal effects, similar to the negative control. These findings suggest that P. foetida leaf extract, especially at higher doses, has potential as an anti-inflammatory agent in sepsis management. The bioactive compounds in the extract, including flavonoids, alkaloids, and terpenoids, likely contribute to its efficacy. This study provides preliminary evidence supporting the use of P. foetida as a potential herbal alternative for managing sepsis, but further clinical research is necessary to confirm its therapeutic potential.